2005
DOI: 10.1136/oem.2004.014738
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk among Finnish cabin attendants: a nested case-control study

Abstract: Background: Earlier studies have found increased breast cancer risk among female cabin crew. This has been suggested to reflect lifestyle factors (for example, age at first birth), other confounding factors (for example, age at menarche), or occupational factors such as exposure to cosmic radiation and circadian rhythm alterations due to repeated jet lag. Aims: To assess the contribution of occupational versus lifestyle and other factors to breast cancer risk among cabin attendants in Finland. Methods: A stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 23 publications
1
54
1
Order By: Relevance
“…We identified 21 individual studies found eligible for metaanalyses of breast and/or prostate cancer in flight personnel (Pukkala et al 1995;Band et al 1996;Lynge 1996;Wartenberg and Stapleton 1998;Gundestrup and Storm 1999;Irvine and Davies 1999;Rafnsson et al 2000;Haldorsen et al 2001;Rafnsson et al 2001;Ballard et al 2002;Blettner et al 2002;Hammar et al 2002;Reynolds et al 2002;Zeeb et al 2002;Linnersjo et al 2003;Paridou et al 2003;Rafnsson et al 2003;Kojo et al 2005) and 9 individual studies with information about breast or prostate cancer risks in shift workers (Tynes et al 1996;Davis et al 2001;Hansen 2001;Schernhammer et al 2001;Kubo et al 2006;Lie et al 2006;O'Leary et al 2006;Schernhammer et al 2006;Conlon et al 2007). Pooled analyses using original data sets from Nordic countries (Pukkala et al 2002 and across Europe Zeeb et al 2003) were not considered in view of a significant overlap with the selected individual studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 21 individual studies found eligible for metaanalyses of breast and/or prostate cancer in flight personnel (Pukkala et al 1995;Band et al 1996;Lynge 1996;Wartenberg and Stapleton 1998;Gundestrup and Storm 1999;Irvine and Davies 1999;Rafnsson et al 2000;Haldorsen et al 2001;Rafnsson et al 2001;Ballard et al 2002;Blettner et al 2002;Hammar et al 2002;Reynolds et al 2002;Zeeb et al 2002;Linnersjo et al 2003;Paridou et al 2003;Rafnsson et al 2003;Kojo et al 2005) and 9 individual studies with information about breast or prostate cancer risks in shift workers (Tynes et al 1996;Davis et al 2001;Hansen 2001;Schernhammer et al 2001;Kubo et al 2006;Lie et al 2006;O'Leary et al 2006;Schernhammer et al 2006;Conlon et al 2007). Pooled analyses using original data sets from Nordic countries (Pukkala et al 2002 and across Europe Zeeb et al 2003) were not considered in view of a significant overlap with the selected individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, except for the standardization of incidence and mortality (for age, calendar period), a classic epidemiological method for the comparison of rates, only two investigations considered possibly relevant covariates of breast Kojo et al 2005) and prostate cancer. Once again, the lack of control of relevant covariates can be explained by the fact that the vast majority of epidemiological investigations was not designed to capture possible breast or prostate cancer risks through CD.…”
Section: Challengesmentioning
confidence: 99%
“…Rafnsson et al (83) reported an increasing risk of breast cancer as the length of employment increased among Icelandic cabin attendants flying long-haul international flights in the pre-jet period, but no trend was evident after jet planes were introduced. Kojo et al (68) showed no evidence that the risk of breast cancer increased as the number of long-haul flights increased among Finnish female cabin attendants.…”
Section: Contributory Evidencementioning
confidence: 97%
“…In case of studies on flight attendants (156)(157)(158)(159)(160)(161)(162)(163)(164)(165)), some of whom tested positive for breast cancer (table 2), many authors claimed the possible concomitant exposure was associated with other risk factors, such as cosmic radiation and jetlag, although no study could report any quantification. This was also the case for the radio and telegraph operators investigated by Tynes et al (8), for whom "shift work highly reflects frequent presence in the radio room both at night and during the day, with possible exposure to light at night, and RF [radio frequency] and ELF [extremely low frequency] fields.…”
Section: Costa Et Almentioning
confidence: 99%